The Use of Snakehead Fish (Channa striata) Bioindicat ors from Taliwang Swamp Lake to Determine Mercury (Hg) 2025 - Murthi, I Wayan Aditya Arya; Khairuddin, Khairuddin; Yamin, M. (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Taliwang Swamp Lake is a source of livelihood for the people of West Sumbawa. High levels of local activity, such as agriculture and mining, have the potential to pollute the lake with mercury (Hg) due to waste from the amalgamation process and fertilizer residues flowing into the lake. This study aims to determine the heavy metal content of mercury (Hg) in snakehead fish (Channa striata) from Rawa Taliwang Lake and its suitability for consumption. Sampling was carried out using a purposive sampling technique at both stations. The criteria for selecting the sampling location were that it could represent the west and east sides of the lake and also take into account the fishing points that could be accessed, considering that the lake was partly covered with vegetation. Data analysis included determining mercury (Hg) levels using a mercury analyzer. The results showed that the mercury (Hg) content in snakehead fish was 0.078 mg/kg. This level is still suitable for consumption according to Food and Drug Supervisory Agency (BPOM) regulation No. 9 of 2022.